Survey of Brain Abnormality using Gabor Wavelets (International Journal of Engineering and Computer Science, 2017)
Nowadays, MR images are very important for automatic defects detection in many diagnostic and therapeutic applications. This available work categorized the brain tissues as normal or abnormal automatically, using computer vision. This paper introduces novel approach of strong automatic diagnostic system using Gabor Wavelets and to find accuracy of tumor diagnosis in brain. Here we are tried to give clear justification from brain tissues using Gabor wavelets, entropy, contrast, energy and statistic features (such as mean, median etc.).